MRI in the evaluation of rotator cuff tendons in chronic shoulder pain - Karki, Subindra; Paudel, Ram Chandra; Phuyal, Arun; Dahal, Mohit Raj (Journal of Chitwan Medical College, 2021)
Background: Shoulder pain is the third most common cause of non- traumatic musculoskeletal pain with rotator cuff pathology being the most common cause. Magnetic Resonance Imaging (MRI) is the imaging modality of choice which helps in accurate diagnosis for making a treatment plan as wrong treatment strategy may lead to poor prognosis. Methods: A descriptive prospective study conducted in 100 individuals with non-traumatic chronic shoulder pain referred to referred to Department of Radiodiagnosis and Imaging, Dhulikhel Hospital, Kavre between 27th August 2020 to 29th August 2021. MRI images were acquired and analyzed by using IBM SPSS 21.0 version Pearson correlation coefficient, Spearman correlation and chi square tests were used for statistical analysis. Results: Rotator cuff pathology was most commonly encountered with supraspinatus being the most frequently involved tendon seen in 28(63.6%), followed by subscapularis 10(22.7%), infraspinatus 4(9%) and teres minor 2(4.5%).Similarly, MRI detected partial tear of supraspinatus in 23(52.2%),partial tear of subscapularis in 8(18.1%),partial tear of infraspinatus in 3(6.8%) and partial tear of teres minor in 2(4.5%) patients. Likewise, complete tear of supraspinatus was observed in 5(11.3%), complete tear of subscapularis in 2(4.5%) and complete tear of infraspinatus in 1(2.2%). Conclusions: Rotator cuff pathologies were the most common causes of chronic shoulder pain, predominantly partial tear of supraspinatus, followed by subscapularis, infraspinatus and teres minor. Magnetic resonance imaging has become the gold standard for diagnostic imaging of the shoulder related to soft tissue injury.